The Role of International Organizations and Conventions in Legal Protection Efforts against Women Victims of ISIS Slavery - Prasetya, Ida Ayu Vera (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 7 No 3 (2018), 2018)
Generally, women have physical not as strong as men and always considered weak so often victimized by crime, aside from sexual slavery by ISIS. Sexual slavery by ISIS includes the category of crime against humanity and desecration of women’s dignity. Slavery is one of the most obvious signs to control and rule others. Therefore, legal protection is needed to alleviate the sadness and suffering women victims of sexual slavery by ISIS. This research aims to know the justification of ISIS thought to make women as sexual slaves and analyze the legal protection effort that can be given to women as victims of ISIS Sexual Slavery by the international organization and international convention. This research is normative legal research. The results of the research indicate the justification of ISIS thought to make women as sexual slaves is a woman who is made as sexual slavery is considered clean so that can enter the heaven. The legal protection effort that can be given to women victims of ISIS sexual slavery by international organization and international convention, one of them is proclaim the protection of human rights with annual review, closing all ISIS access to financial system, working with several countries, especially Canada and Germany in the emergency countermeasures relief programme for the victim, provide psychosocial support services shape training to overcome their problems, and establish social cooperation by encouraging the International Government to strengthen security in an area whose women are the most victims of ISIS sexual slavery.